Enlarging the Application of the Food Security Index at European Union Regions - Mihoreanu, Larisa; Cismas, Laura Mariana; Danila Jianu, Laura Maria (Journal of Economic Development, Environment and People, 2019)
The food security remains a major priority and a typical issue that requires immediate international solutions. Recent studies reveal the increasing complexity of food security issues focusing on the necessity to address formal actions and solve the dramatic situations. New tools are always welcome to facilitate solutions’ implementation. In September 2015, the United Nations Assembly adopted the 2030 Agenda of Sustainable Development among the goals of which the followings are fundamental: no poverty, zero hunger, good health and well-being, clean water and climate action. The European Union joined the Program, expressing the full commitment to its implementation. According to the Food and Agriculture Organization (FAO), the number of undernourished people reached in 2017 about 821 million peoples, representing an increase from about 804 million peoples in 2016. The 2018 statistics of FAO state that 22% of children under-five are affected by malnutrition, while over 38 million children in the same age group are overweight. Beyond the premises, as a novelty, we contribute at the food security knowledge by calculating a regional index at European and Romanian levels to better outline the realities and provide the decision-makers with a new tool to find better solutions.